On the brink and at the world's edge: Western approaches to Central Asia's international politics, 1991–2021. Issue 4 (2nd October 2021) - Cooley, Alexander
ABSTRACT: Western scholarship on the foreign policies of the post-Soviet Central Asian states has consistently framed the region as marginalized but ripe for Great Power influence and poised to assume a more important role in world affairs. This article explores the analytical assumptions, institutional agendas, and geopolitical drivers of scholarly and policy portrayals of Central Asia, emphasizing the key role played by the Western military intervention in Afghanistan in 2001 and the region's supporting role as logistics providers and security partners. The ensuing local and regional reactions to this intensifying securitization prompted International Relations scholars to explore the limits of Western governance and the liberal international order in Central Asia and highlight the rise of new counter-ordering norms, organizations and networks. This body of work has made important contributions to the now growing literature on post-Western International Relations, but still excludes the voices of many Central Asian scholars themselves and overlooks important regional topics and new analytical approaches.